Endothelial Nitric Oxide Production and Antioxidant Response in Breath-Hold Diving: Genetic Predisposition or Environment Related? - Cialoni, Danilo; Brizzolari, Andrea; Samaja, Michele; Bosco, Gerardo; Paganini, Matteo; Sponsiello, Nicola; Lancellotti, Valentina; Marroni, Alessandro (Frontiers in Physiology, 2021)
Introduction: Nitric oxide (NO) is an essential signaling molecule modulating the endothelial adaptation during breath-hold diving (BH-diving). This study aimed to investigate changes in NO derivatives (NOx) and total antioxidant capacity (TAC), searching for correlations with different environmental and hyperbaric exposure. Materials and methods: Blood samples were obtained from 50 breath-hold divers before, and 30 and 60 minutes after the end of training sessions performed both in a swimming pool or the sea. Samples were tested for NOx and TAC differences into different groups related to their hyperbaric exposure, experience and additional genetic polymorphism. Results: We found statistically significant differences in NOx plasma concentration during the follow-up (decrease at T30 and increase at T60) compared to the pre-dive values. At T30, we found a significantly lower decrease of NOx in subjects with a higher diving experience, but no difference was detected between the swimming pool and Sea. No significant difference was found in TAC levels, as well as between NOx and TAC levels and the genetic variants. Conclusions: Our data showed how NO consumption in BH-diving is significantly lower in the expert group, indicating a possible training-related adaptation process. Data confirm a significant NO use during BH-diving, compatible with the well-known BH-diving related circulatory adaptation suggesting that the reduction in NOx 30 minutes after diving can be ascribed to the lower NO availability in the first minutes after the dives. Expert BH-divers suffered higher oxidative stress. A preliminary genetic investigation seems to indicate a less significant influence of genetic predisposition.